Optimal Cross-Licensing Arrangements: Collusion versus Entry Deterrence - Jay Pil Choi; Heiko Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyzes optimal cross-licensing arrangements between incumbent firms in the presence of potential entrants. The optimal cross-licensing royalty rate trades off incentives to sustain a collusive outcome vis-a-vis incentives to deter entry with the threat of patent litigation. We show that a positive cross-licensing royalty rate, which would otherwise relax competition and sustain a collusive outcome, dulls incentives to litigate against entrants. Our analysis can shed light on the puzzling practice of royalty free cross-licensing arrangements between competing firms in the same industry as such arrangements enhance incentives to litigate against any potential entrants and can be used as entry-deterrence mechanism.
Keywords: D43; L13; O30; 330; cross-licensing arrangements; patent litigation; collusion; entry deterrence